2004
DOI: 10.1097/01.ccm.0000104919.07538.04
|View full text |Cite
|
Sign up to set email alerts
|

N,N′,N′-triacetylglucosamine, an inhibitor of lysozyme, prevents myocardial depression in Escherichia coli sepsis in dogs*

Abstract: We found that TAC, a competitive inhibitor of Lzm-S, prevented myocardial depression in experimental sepsis. Only specific NAG structures are inhibitory to Lzm-S's depressant activity. TAC may be useful in attenuating cardiovascular collapse in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The in vivo contribution of Lzm-S to cardiovascular collapse in this condition was previously demonstrated in our E. coli sepsis model, in which chitotriose (N,NЈ,N"-triacetylchitotriose), an inhibitor of Lzm-S, prevented the fall in mean arterial blood pressure, cardiac output, and stroke work otherwise observed (29). We also found that chitotriose could inhibit the Lzm-S-induced decrease in FSR in the RVT preparation (28).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The in vivo contribution of Lzm-S to cardiovascular collapse in this condition was previously demonstrated in our E. coli sepsis model, in which chitotriose (N,NЈ,N"-triacetylchitotriose), an inhibitor of Lzm-S, prevented the fall in mean arterial blood pressure, cardiac output, and stroke work otherwise observed (29). We also found that chitotriose could inhibit the Lzm-S-induced decrease in FSR in the RVT preparation (28).…”
Section: Discussionsupporting
confidence: 61%
“…The mechanism seems to relate to relatively enhanced stimulation of the parasympathetic system that can be blocked by atropine. On the basis of our in vitro and in vivo experiments (18,(27)(28)(29), we therefore suggest that inhibitors of Lzm-S, by improving SS contraction and the neural adrenergic response, offer a potential strategy for the reversal of cardiovascular collapse in septic shock.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…48 In extension of these findings, ultrafiltrates from patients with severe sepsis and simultaneously reduced left ventricular stroke work index (Ͻ30 g · m Ϫ1 · m Ϫ2 ) displayed cardiotoxic effects and contained significantly increased concentrations of interleu-kin (IL)-1, IL-8, and C3a. 49 Recently, Mink et al 50 demonstrated that lysozyme c, a bacteriolytic agent believed to originate mainly from disintegrating neutrophilic granulocytes and monocytes, mediates cardiodepressive effects during Escherichia coli sepsis and, importantly, that competitive inhibition of lysozyme c can prevent myocardial depression in the respective experimental sepsis model. Additional potential candidates for myocardial depressant substance include other cytokines, prostanoids, and nitric oxide (NO).…”
Section: Myocardial Depressant Substancementioning
confidence: 99%
“…We previously found that lysozyme (Lzm-S), released from leukocytes, contributed to the myocardial depression that develops in canine models of septic shock (21,(33)(34)(35). We showed that the mechanism by which Lzm-S caused myocardial depression was related to the binding of its catalytic site to the endocardial endothelium (EE) (33).…”
mentioning
confidence: 99%